ENHANCING ARABIC NOVEL COMPREHENSION THROUGH MOBILE-ASSISTED LEARNING: DUOLINGO IN AN ISLAMIC STUDIES CONTEXT - Osman, Rahmah Ahmad H.; Che Ibrahim, Siti Umira; Yaapar, Md. Salleh; Ali, Adham Hamawiya; Che Amran, Aisyah Aminah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The comprehension of Arabic novels presents a persistent challenge for learners of Arabic as a foreign language, particularly students enrolled in Islamic studies programmes in non-Arab contexts. Arabic narrative texts are linguistically complex and culturally embedded, requiring advanced vocabulary knowledge, syntactic awareness, and interpretive competence. In recent years, mobile-assisted language learning applications such as Duolingo have gained popularity among students as supplementary tools for Arabic learning. While previous research has demonstrated the effectiveness of Duolingo in supporting vocabulary acquisition, grammatical development, and learner motivation, its role in facilitating literary comprehension remains insufficiently explored. This study investigates the extent to which Duolingo supports undergraduate Islamic studies students’ comprehension of Arabic novels within a blended learning context. Adopting a mixed-methods research design, the study draws on questionnaire data, semi-structured interviews, and thematic analysis to examine students’ experiences, perceived benefits, and limitations of using Duolingo alongside traditional instructional practices. The findings indicate that Duolingo contributes positively to foundational linguistic development and learner motivation, thereby reducing initial barriers to reading Arabic novels. However, the application is limited in supporting discourse-level comprehension, cultural contextualisation, and literary interpretation, which are essential for meaningful engagement with narrative texts. The study argues that Duolingo is most effective when positioned as a preparatory and supplementary tool within a blended pedagogical framework. By clarifying the pedagogical affordances and constraints of mobile-assisted language learning in literary contexts, this study contributes to research in Arabic as a Foreign Language and offers practical implications for the teaching of Arabic novels to non-native learners.